RESPON PERTUMBUHAN DAN HASIL PADI VARIETAS IR NUTRIZINC TERHADAP APLIKASI BIOCHAR DAN BENZILADENIN - Rafika, Eni; Yusnita, Yusnita; Karyanto, Agus; Hapsoro, Dwi; Pramono, Eko (JURNAL AGROTROPIKA, 2025)
Rice growth and yield can be increased through various efforts, including the use of "high-yielding varieties, fertilization, soil conditioners with application of plant growth regulators (PGRs). Soil conditioners namely as biochar are carbon products that can enhance plant productivity through enhancing the physical, chemical, and biological characteristics of the soil, while cytokinine benzyladenine (BA) is a PGR that has been widely documented to stimulate cell growth, cell division, and differentiation in rice plants. The purpose of this study was to determine the effect of biochar and benzyladenine (BA) on the growth and yield of the IR Nutrizinc rice variety. Data collection was carried out in October 2024 - February 2025 in Kampung Payung Rejo, Pubian District, Central Lampung Regency. The treatments were arranged factorially (2x3) using a completely randomized design with 3 replications. Factor I was without biochar and given 20 tons/ha of biochar. The second factor was 3 benzladenin (BA) concentrations, namely 0 ppm, 50 ppm, and 100 ppm applied by spraying on the surface of the plant at 20, 30, and 40-days after transplanting, while the biochar application was implemented 2 weeks before transplanting. Observed variables included plant height, maximum tillers per clump, count of productive tillers, length of panicles, and grains per panicle, percentage of empty grains per panicle, dry harvested grain yield, dry harvest grain yield, 1000 grain weight and dry weight of the crownThe Bartlett test was employed to assess the homogeneity of variance among treatments then analysis of variance was carried outIf a notable difference existed between treatments, the BNT test was carried out at the 5% significance level. The findings indicated that applying 20 tons/ha of biochar enhanced the yield components in terms of dry harvested grain, dry milled grain, and dry shoot weight The application of 50 ppm BA was able to increase the growth and yield of grain compared to without benzyladenine (BA). The combination of biochar and BA enhanced the growth and yield of grain in terms of the number of grains per panicle, dry harvested grain, and dry milled grain. The use of 20 tons/ha biochar combined with 50 ppm BA enhanced the yield of the IR Nutrizinc